Dependence of supercapacitor performance on macro-structure of monolithic biochar electrodes. (November 2018) - Caguiat, Johnathon N.; Arpino, Gabriel; Krigstin, Sally G.; Kirk, Donald W.; Jia, Charles Q.
Abstract: Large-scale applications of recalcitrant biochar produced from photosynthetic biomass are considered a "carbon-negative" measure that can help reduce the growing stockpile of atmospheric carbon. One such application is to use biochar as the electrode material in supercapacitors, a fast-charging and long-lasting electrical energy storage device. To facilitate devices' performance, commercial supercapacitor electrodes typically take the form of thin films (∼50 μm) made of activated carbon powder and a binder. Consequently, the fraction of active electrode material is small, as is its energy density. While thickening electrodes increases the fraction of active material, it also raises the resistance to electron and ion transport within the powder-based electrode. It is hypothesized that the use of monolithic biochar will enable thicker electrodes with adequate device performance. In this work, supercapacitor cells were constructed with monolithic biochar electrodes of different orientations and thickness. The specific capacitance and its dependence on current density were measured with a set of electrochemical methods and used to evaluate the performance of these cells. These experiments revealed that the inherent macro-structure of biochar plays a significant role in determining the performance of monolithic biochar electrodes. The dimension of structural features, such as the length of tracheids, can dictate the depth of electrolyte penetration. It is demonstrated that the proper design and manufacturing of monolithic biochar can extend the effective thickness of supercapacitor electrode to ∼1 cm, establishing the feasibility of increasing energy density of supercapacitors by using thick, monolithic biochar. Highlights: Thick monolithic biochar electrodes (up to ∼1 cm) are fabricated and tested. Performance of supercap electrodes is maintained as electrode becomes thicker. The performance retention depends on the inherent structure of the biochar. Large supercapacitor electrodes and thus high energy density devices are feasible.